Pengaruh Akuntansi Konservatisme terhadap Penilaian Equitas dengan Kepemilikan Manajerial sebagai Variabel Moderasi - Delory Nancy Meyla (SAFE-Network, 2023)
This study aims to analyze the accounting conservatism of the value of equity, whether managerial ownership is able to strengthen the relationship of accounting conservatism affect the value of equity in 8 manufacturing companies listed on the Indonesia Stock Exchange (BEI) from the period 2014 to 2017. The sampling method is done by purposive sampling The data used is obtained from data contained in the Indonesia Stock Exchange. Data analysis method in this research uses Moderation multiple linear regression. The results of this study indicate that: Conservatism Accounting Variables (X1). Assessment of Equity (Y) and Managerial Ownership as a moderating variable. Accounting conservatism has a significant effect on the valuation of equity because the sig value of 0.028 is smaller than 0.05. Managerial ownership has a significant effect on the valuation of equity because the sig value of 0.049 is smaller than 0.05. The moderating variable significantly influences the assessment of equity because the sig value of 0.016 is smaller than 0.05.